Efforts to Increase Motivation to Read Recount Text Through Playing Games for Elementary School Children at SDN Koli - Mansuetus Mola (Yayasan Adra Karima Hubbi, 2024)
Background. Traditional methods of teaching recount texts often struggle to engage students effectively. Educational games offer a potential solution to increase motivation and comprehension in language learning, particularly for primary school students. Purpose. This research aims to investigate the effectiveness of educational games in increasing motivation to read recount texts among students at SDN Koli. Method. The study employs a qualitative approach, utilizing QDA Miner software for data analysis. Data collection methods include in-depth interviews, participant observation, and document analysis of classroom teaching and learning activities. The research focuses on exploring students' and teachers' experiences, perceptions, and motivations regarding the use of games in learning. Results. The findings indicate that educational games significantly increase student motivation and engagement in learning recount texts. These games make the learning process more exciting and interactive, helping students better understand story structure and event sequences. In the affective domain, games foster reflection and humility, creating a positive learning environment. Cognitively, the games prove highly effective in improving writing skills and contribute significantly to reading and speaking abilities. While the psychomotor impact is smaller, the games still help students manage emotions and maintain focus. Conclusion. The integration of educational games in teaching recount texts not only enhances cognitive skills but also positively impacts students' affective and psychomotor aspects. This research underscores the importance of innovative learning methods in meeting students' needs in the digital era. By adopting such approaches, educators can nurture a generation of students who are more motivated, skilled, and prepared for future challenges in language learning and beyond.